Shining light on benthic macroalgae: mechanisms of complementarity in layered macroalgal assemblages. - Leigh W Tait; Ian Hawes; David R Schiel (PLoS ONE, 2014)
Phototrophs underpin most ecosystem processes, but to do this they need sufficient light. This critical resource, however, is compromised along many marine shores by increased loads of sediments and nutrients from degraded inland habitats. Increased attenuation of total irradiance within coastal water columns due to turbidity is known to reduce species' depth limits and affect the taxonomic structure and architecture of algal-dominated assemblages, but virtually no attention has been paid to the potential for changes in spectral quality of light energy to impact production dynamics. Pioneering studies over 70 years ago showed how different pigmentation of red, green and brown algae affected absorption spectra, action spectra, and photosynthetic efficiency across the PAR (photosynthetically active radiation) spectrum. Little of this, however, has found its way into ecological syntheses of the impacts of optically active contaminants on coastal macroalgal communities. Here we test the ability of macroalgal assemblages composed of multiple functional groups (including representatives from the chlorophyta, rhodophyta and phaeophyta) to use the total light resource, including different light wavelengths and examine the effects of suspended sediments on the penetration and spectral quality of light in coastal waters. We show that assemblages composed of multiple functional groups are better able to use light throughout the PAR spectrum. Macroalgal assemblages with four sub-canopy species were between 50-75% more productive than assemblages with only one or two sub-canopy species. Furthermore, attenuation of the PAR spectrum showed both a loss of quanta and a shift in spectral distribution with depth across coastal waters of different clarity, with consequences to productivity dynamics of diverse layered assemblages. The processes of light complementarity may help provide a mechanistic understanding of how altered turbidity affects macroalgal assemblages in coastal waters, which are increasingly threatened by diminishing light quantity and altered spectral distributions through sedimentation and eutrophication.